Entrepreneurship and Sustainable Development Goals: An SCT Model Analysis (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study aims to explore how entrepreneurship contributes to achieving the Sustainable Development Goals (SDGs) in Sidoarjo Regency. Methodology: Using a quantitative approach, the research applies the Script Concordance Test (SCT) to assess how well entrepreneurial actions align with sustainability principles. Data were collected from 30 entrepreneurs across various sectors, carefully selected to ensure diverse perspectives. The SCT scores reveal an average alignment of 0.77, reflecting a solid understanding of sustainability among entrepreneurs. Results: The findings demonstrate that entrepreneurship significantly supports SDGs, especially by creating jobs (with a workforce increase of 32%) and improving economic well-being through higher average incomes. However, challenges remain in environmental sustainability, where scores are lower for practices like using eco-friendly materials (0.55) and reducing carbon emissions (0.47). Entrepreneurs cited barriers such as limited access to technology, financial constraints, and insufficient policy support. Novelty: This study is novel in applying SCT to entrepreneurship, offering a fresh perspective on decision-making in sustainability. It highlights the importance of technological innovation and multi-stakeholder collaboration in fostering a thriving, sustainable entrepreneurial ecosystem. Practical Implications: To bridge the gaps, policymakers are encouraged to provide fiscal incentives, enhance digital literacy, and simplify regulatory processes. Collaboration among governments, private sectors, and communities is crucial to empower entrepreneurs and foster sustainable growth. Conclusion: Entrepreneurship is more than an economic driver; it is a force for addressing social and environmental challenges. With the right support and policies, entrepreneurs in Sidoarjo can set a powerful example of how local initiatives contribute to global SDGs. Type of Paper: Empirical Research Paper.